Surface-Enhanced Raman Spectroscopy for Bisphenols Detection: Toward a Better Understanding of the Analyte–Nanosystem Interactions - Roschi, Eleanora; Gellini, Cristina; Ricci, Marilena; Sánchez Cortés, Santiago; Focardi, Claudia; Neri, Bruno; Otero-Fernández-de-Molina, Juan Carlos; López-Tocón, Isabel; Smulevich, Giulietta; Becucci, Maurizio (MDPI, 2021)
Silver nanoparticles functionalized with thiolated β-cyclodextrin (CD-SH) were employed for the detection of bisphenols (BPs) A, B, and S by means of surface-enhanced Raman spectroscopy (SERS). The functionalization of Ag nanoparticles with CD-SH leads to an improvement of the sensitivity of the implemented SERS nanosensor. Using a multivariate analysis of the SERS data, the limit of detection of these compounds was estimated at about 10−7 M, in the range of the tens of ppb. Structural analysis of the CD-SH/BP complex was performed by density functional theory (DFT) calculations. Theoretical results allowed the assignment of key structural vibrational bands related to ring breathing motions and the inter-ring vibrations and pointed out an external interaction due to four hydrogen bonds between the hydroxyl groups of BP and CD located at the external top of the CD cone. DFT calculations allowed also checking the interaction energies of the different molecular species on the Ag surface and testing the effect of the presence of CD-SH on the BPs’ affinity. These findings were in agreement with the experimental evidences that there is not an actual inclusion of BP inside the CD cavity. The SERS sensor and the analysis procedure of data based on partial least square regression proposed here were tested in a real sample consisting of the detection of BPs in milk extracts to validate the detection performance of the SERS sensor.
Keywords: Espectroscopia Raman; Ciclodextrinas; Fenoles; SERS; DFT calculations; Cyclodextrin; Bisphenol A; Bisphenol S; Bisphenol B